"Quality-by-Design" approach to the development of a dosage form for the liposomal delivery system of cytochrome С - Katsai, O. G.; Ruban, O. A.; Krasnopolsky, Yu. M. (Hellenic Pharmaceutical Society, 2018)
Cytochrome C (Cyt C) is a natural catalyst for cellular respiration. Aqueous solutions of Cyt C are used in cardiology, neurology and ophthalmology, where they manifests a high activity towards free radicals and bind aggressive molecules of oxidants. The aim of the study was to develop and optimize the preparation of freeze-dried cytochrome C-containing liposomes (FD-Cyt-LS) using the Quality by Design (QbD) approach and to compare the stability of aqueous Cyt-LS and FD-Cyt-LS. In the case of freeze-dried Cyt-LS (FD-Cyt-LS), the influence of cryoprotectants type and concentration, as well as secondary drying temperature, which ensure integrity of liposomal membrane during lyophilization and preservation throughout the shelf life were studied. Lactose with a concentration of 6% was established to be the optimal type of cryoprotectant. At the lyophilization programme selected the most preferable secondary drying temperature value was 30°C. The necessity to choose the form of lyophilizate for solution preparation was shown with the example of stability evaluation of aqueous Cyt-LS and FD-Cyt-LS. During the observation period, aqueous Cyt-LS shows the growth of degradation products of free fatty acids and lysophosphatidylcholine (LPC) by 202.5% and 409.7% respectively, compared with the reference values, as well as the decrease of the content of phosphatidylcholine (РС) and dipalmitoylphosphatidylcholine (DPPG- Na) by 1.5 and 1.0%, respectively. At the same time, no significant changes in the composition of FD-Cyt-LS samples were observed.
Keywords: liposome; QbD; cytochrome C; lyophilization; freeze-dried